The Influence of Debt Levels, Operating Cash Flow, and Firm Size on Earnings Persistence - Haqqi, Arif Aulia; Hizazi , Achmad; Yetti , Susfa (Jurnal Cakrawala Akuntansi, 2024)
This study aims to examine the influence of debt levels, operating cash flow, and firm size on earnings persistence. The research population includes companies in the Basic Industry and Chemicals sector listed on the Indonesia Stock Exchange (IDX) during the period 2015–2018. A purposive sampling method was applied, resulting in a final sample of 59 companies with a total of 236 firm-year observations. The data were analyzed using multiple linear regression techniques.The empirical findings reveal that debt levels have no significant effect on earnings persistence. In contrast, operating cash flow and firm size exhibit a significant positive influence on earnings persistence. Furthermore, the variables tested—debt levels, operating cash flow, and firm size—are shown to have a joint effect on earnings persistence, with an Adjusted R-Square value of 0.033. This indicates that only 3.3% of the variation in earnings persistence can be explained by the model, while the remaining 96.7% is influenced by other factors not included in this study.This study contributes to the accounting and finance literature by highlighting the limited explanatory power of firm-level financial indicators—particularly debt levels—in predicting earnings persistence in the manufacturing sector. The findings underscore the importance of internal performance indicators such as operating cash flow and firm size in assessing the sustainability of earnings over time.